A Quality control systems study on the Philippine Standard - Castaneda, Romeo; Ibana, Enrico; Kintanar, Tagumpay; Manalang, Grace; Natividad, Mamerto; Taylor, Carlos (College of Engineering, 1982)
In fulfillment of the requirements and objectives of the IE 135 course,The group chose Liwayway Publishing Inc.as its main plant site.After a few meetings with Mr. Roger Mendoza,Asst.Production Manager of the said company,the group decided to conduct a statistical quality control study on any magazine or newspaper published by the company as long as it conforms to the needed qualifications in the study.Preliminary observations during the course of visits proved that Balita was ideal focal point for the study because of the daily continuous production system.Data gathering and personnel interviews were then conducted during production runs which normally starts at about 9:30 P.M. and ends usually at 4:00 A.M.Due to irregularity in the production volume,the p-chart was decided to be fundamental tool for observations and recommendations.Interviews with the operators and pressmen during the production run provided the group with additional information regarding equipment function and personnel roles.After enough data and information were collected the p-chart was evaluated and alternatives/recommendations given by each member during brainstorming sessions.The final set of recommendations arrived at by the group are:1.use of p-chart to record and evaluate the performance of production per run as its wastage level.2.Implementation of an incentive policy which will reduce wastage via the workers' initiative.